1987
DOI: 10.1007/bf01412755
|View full text |Cite
|
Sign up to set email alerts
|

The viscoelastic properties of wool and the influence of some specific plasticizers

Abstract: Abstract:The relaxation behaviour of Lincoln wool fibres in water and in three short chain aliphatic alcohols was measured. Applying a two phase model including a relaxation function based on a log-normal distribution of relaxation times a good systematic description of the data was found. The application of the model to the relaxation curves of wool fibers in the alcoholic media showed the invariance of the shape of the relaxation function, its shift on the log-time scale and the change of the elastical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This effect is due to the pronounced plasticizer action of water on the matrix material (Haly and Snaith, 1967;Wortmann, 1987;Cao and Leroy, 2005;Wortmann et al, 2006b). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is due to the pronounced plasticizer action of water on the matrix material (Haly and Snaith, 1967;Wortmann, 1987;Cao and Leroy, 2005;Wortmann et al, 2006b). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In analogy to the case of extensional relaxation14, 19, 28 time‐dependent bending stiffness is described by: …”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations for α‐keratinous materials14, 19, 28, 29 and various other polymers30, 31 have successfully made use of the cumulative log‐normal distribution (CLND) as relaxation function. An obvious, practical disadvantage of the CLND function is the lack of an analytical form, necessitating the use of numerical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wortmann [158] In the intermediate filaments/matrix model, the matrix is mainly consisted of noncrystalline component, which is accessible to water. It has been found that the modulus of matrix decreases significantly at the presence of moisture [159,163], and such a phenomenon is attributed to the strong plasticizing effect of water on matrix [164][165][166][167]. In the contrast, the intermediate filaments contains α-helical component and is highly organized [168].…”
Section: Natural Biomaterials As Potential Shape Memory Materialsmentioning
confidence: 99%